2017
DOI: 10.1590/0102-311x00213315
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of motives underlying food choice and barriers to healthy eating among low medium income consumers in Uruguay

Abstract: Interventions aimed at changing dietary patterns should be designed based on the main motives underlying the food choices of specific target populations. The aim of the present study was to identify motives underlying food choice and barriers to healthy eating among consumers in two socioeconomic levels in Uruguay. Eleven focus groups were carried out with a total of 76 participants. Six of the groups involved low income participants and the others were conducted with middle income participants. Discussions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 40 publications
2
24
0
7
Order By: Relevance
“…This high acceptance is possibly explained by the high sweetness of this sample (industrially added by sugar and noncaloric sweeteners), as Brazilians are used to drinking juice with sugar content (Reis et al, ). Additionally, high PDM acceptance can be explained by consumption habits related to the fact that it is easy to make and inexpensive, which is commonly observed for a low‐income population (Ares, Machín, Girona, Curutchet, & Giménez, ). All the remaining samples showed low acceptation, whereby NFC and UHT were similar showing scores for all attributes around 3.94–5.86, and FCOJ and FLC were the most rejected ones, with scores between 2.41 and 5.55, possibly due to the low brix of these samples after dilution.…”
Section: Resultsmentioning
confidence: 99%
“…This high acceptance is possibly explained by the high sweetness of this sample (industrially added by sugar and noncaloric sweeteners), as Brazilians are used to drinking juice with sugar content (Reis et al, ). Additionally, high PDM acceptance can be explained by consumption habits related to the fact that it is easy to make and inexpensive, which is commonly observed for a low‐income population (Ares, Machín, Girona, Curutchet, & Giménez, ). All the remaining samples showed low acceptation, whereby NFC and UHT were similar showing scores for all attributes around 3.94–5.86, and FCOJ and FLC were the most rejected ones, with scores between 2.41 and 5.55, possibly due to the low brix of these samples after dilution.…”
Section: Resultsmentioning
confidence: 99%
“…However, the AHEI scores may relate to the sample composition with respect to socioeconomic status. In fact, it has been reported that families from lower socioeconomic backgrounds may not have access to or be able to afford nutritious food for their children 5,36 . This reality also relates to the fact that the high cost of healthy food is an important barrier in promoting healthy eating behaviors 21,36 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been reported that families from lower socioeconomic backgrounds may not have access to or be able to afford nutritious food for their children 5,36 . This reality also relates to the fact that the high cost of healthy food is an important barrier in promoting healthy eating behaviors 21,36 . Nevertheless, the significantly higher AHEI and SWFoL scores from Group 1 compared to Groups 2 and 3 confirm the relationship between greater levels of foodrelated life satisfaction and better eating habits 2,5 , although the association between life satisfaction and better or worse eating habits was confirmed only in Groups 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Uruguay confirmed the influence of income level on the underlying FCM and barriers to the adoption of healthy eating between low and middle SEC. It was found that low SEC respondents described their choices as mainly driven by economic factors and physical needs (e.g., satiety), whereas product-related characteristics (i.e., convenience) were mainly determined for middle SEC respondents [40].…”
Section: Introductionmentioning
confidence: 97%